Hydrogen Sulfide Mitigates Kidney Injury in High Fat Diet-Induced Obese Mice. (19th June 2016) - Wu, Dongdong; Gao, Biao; Li, Mengling; Yao, Ling; Wang, Shuaiwei; Chen, Mingliang; Li, Hui; Ma, Chunyan; Ji, Ailing; Li, Yanzhang
Abstract : Obesity is prevalent worldwide and is a major risk factor for the development and progression of kidney disease. Hydrogen sulfide (H2 S) plays an important role in renal physiological and pathophysiological processes. However, whether H2 S is able to mitigate kidney injury induced by obesity in mice remains unclear. In this study, we demonstrated that H2 S significantly reduced the accumulation of lipids in the kidneys of high fat diet- (HFD-) induced obese mice. The results of hematoxylin and eosin, periodic acid-Schiff, and Masson's trichrome staining showed that H2 S ameliorated the kidney structure, decreased the extent of interstitial injury, and reduced the degree of kidney fibrosis in HFD-induced obese mice. We found that H2 S decreased the expression levels of tumor necrosis factor- α, interleukin- (IL-) 6, and monocyte chemoattractant protein-1 but increased the expression level of IL-10. Furthermore, H2 S treatment decreased the protein expression of p50, p65, and p-p65 in the kidney of HFD-induced obese mice. In conclusion, H2 S is able to mitigate renal injury in HFD-induced obese mice through the reduction of kidney inflammation by downregulating the expression of nuclear factor-kappa B. H2 S or its releasing compounds may serve as a potential therapeutic molecule for obesity-induced kidney injury.